2013
DOI: 10.1186/1745-6215-14-145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and development of a novel binocular treatment (I-BiT™) system using video clips and interactive games to improve vision in children with amblyopia (‘lazy eye’): study protocol for a randomised controlled trial

Abstract: BackgroundAmblyopia (lazy eye) affects the vision of approximately 2% of all children. Traditional treatment consists of wearing a patch over their ‘good’ eye for a number of hours daily, over several months. This treatment is unpopular and compliance is often low. Therefore results can be poor. A novel binocular treatment which uses 3D technology to present specially developed computer games and video footage (I-BiT™) has been studied in a small group of patients and has shown positive results over a short pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 9 publications
1
20
0
1
Order By: Relevance
“…16 The study was a randomised parallel group design with the intention to recruit 75 patients. The eligible patients were randomised to one of three treatments.…”
Section: Materials and Methods Trial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The study was a randomised parallel group design with the intention to recruit 75 patients. The eligible patients were randomised to one of three treatments.…”
Section: Materials and Methods Trial Designmentioning
confidence: 99%
“…For full list of inclusion and exclusion criteria, see the protocol paper. 16 Interventions I-BiT shutter glasses system…”
Section: Participants and Recruitmentmentioning
confidence: 99%
“…An interactive binocular treatment, the I-BiT, has also been described. [21][22][23][24] The I-BiT presents equal-contrast central stimuli to the amblyopic eye and peripheral stimuli to the fellow eye. A pilot study on nine children who used the I-BiT for 30 min per week for 6 weeks reported that six had 0.125 logMAR or more improvement in visual acuity but had no control group.…”
Section: Discussionmentioning
confidence: 99%
“…La numérisation de ces tests peut permettre d'améliorer les conditions de travail des orthoptistes, proposer des tests originaux avec une précision accrue, rendre les examens plus rapides et pourquoi pas, permettre une large autonomie du patient. Seuls quelques tests orthoptiques numériques sont disponibles sur le marché de nos jours [2] tandis que d'autres ne sont que des prototypes [3][4][5][6][7][8][9][10]. La société Orthoptica ® développe des tests oculomoteurs sur une plateforme numérique utilisant un dérivé de la technologie du cinéma 3D en utilisant en écran, un projecteur et des lunettes actives [11].…”
Section: Introductionunclassified